Electrical characterization of defects introduced during electron beam deposition of W Schottky contacts on n-type 4H-SiC. (15th August 2016) - Omotoso, E.; Meyer, W.E.; Coelho, S.M.M.; Diale, M.; Ngoepe, P.N.M.; Auret, F.D.
Abstract: We have studied the defects introduced in n -type 4H-SiC during electron beam deposition (EBD) of tungsten by deep-level transient spectroscopy (DLTS). The results from current-voltage and capacitance-voltage measurements showed deviations from ideality due to damage, but were still well suited to a DLTS study. We compared the electrical properties of six electrically active defects observed in EBD Schottky barrier diodes with those introduced in resistively evaporated material on the same material, as-grown, as well as after high energy electron irradiation (HEEI). We observed that EBD introduced two electrically active defects with energies EC – 0.42 and EC – 0.70 eV in the 4H-SiC at and near the interface with the tungsten. The defects introduced by EBD had properties similar to defect attributed to the silicon or carbon vacancy, introduced during HEEI of 4H-SiC. EBD was also responsible for the increase in concentration of a defect attributed to nitrogen impurities (EC – 0.10) as well as a defect linked to the carbon vacancy (EC – 0.67). Annealing at 400 °C in Ar ambient removed these two defects introduced during the EBD.